DEVELOPED COUNTRIES’ TAXATION MODELS, DIFFERENCES AND THEIR IMPLEMENTATIONS IN OTHER COUNTRIES. (Ustozlar uchun, 2024)
Abstract: This thesis encompasses various ways to develop tax system by utilizing the tactics which have been being used by developed countries for many years.